2011
DOI: 10.1242/jcs.078790
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the βA3/A1-crystallin gene impairs phagosome degradation in the retinal pigmented epithelium of the rat

Abstract: Phagocytosis of the shed outer segment discs of photoreceptors is a major function of the retinal pigmented epithelium (RPE). We demonstrate for the first time that βA3/A1-crystallin, a major structural protein of the ocular lens, is expressed in RPE cells. Further, by utilizing the Nuc1 rat, in which the βA3/A1-crystallin gene is mutated, we show that this protein is required by RPE cells for proper degradation of outer segment discs that have been internalized in phagosomes. We also demonstrate that in wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 44 publications
0
81
0
Order By: Relevance
“…Cytoskeletal rearrangements occur through the evolutionarily conserved ELMO1 (engulfment and cell motility protein 1)-DOCK180 (dedicator of cytokinesis)-RAC complex (Elliott and Ravichandran, 2010). We have reported that some of these proteins, such as ELMO1, DOCK 180 and RAC1 are also expressed in the RPE cells of the rat, indicating that a similar signaling pathway may be involved in phagosome maturation in RPE (Zigler et al, 2011). We have also shown that Rab5 GTPase, which in macrophages is known to be crucial in the final maturation process before the degradation by lysosomal enzymes occurs, is also important in the maturation process in RPE (Zhou and Yu, 2008; Zigler et al, 2011).…”
Section: 0 Phagocytosis In the Retinal Pigment Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoskeletal rearrangements occur through the evolutionarily conserved ELMO1 (engulfment and cell motility protein 1)-DOCK180 (dedicator of cytokinesis)-RAC complex (Elliott and Ravichandran, 2010). We have reported that some of these proteins, such as ELMO1, DOCK 180 and RAC1 are also expressed in the RPE cells of the rat, indicating that a similar signaling pathway may be involved in phagosome maturation in RPE (Zigler et al, 2011). We have also shown that Rab5 GTPase, which in macrophages is known to be crucial in the final maturation process before the degradation by lysosomal enzymes occurs, is also important in the maturation process in RPE (Zhou and Yu, 2008; Zigler et al, 2011).…”
Section: 0 Phagocytosis In the Retinal Pigment Epithelial Cellsmentioning
confidence: 99%
“…We have reported that some of these proteins, such as ELMO1, DOCK 180 and RAC1 are also expressed in the RPE cells of the rat, indicating that a similar signaling pathway may be involved in phagosome maturation in RPE (Zigler et al, 2011). We have also shown that Rab5 GTPase, which in macrophages is known to be crucial in the final maturation process before the degradation by lysosomal enzymes occurs, is also important in the maturation process in RPE (Zhou and Yu, 2008; Zigler et al, 2011). Information regarding the role of the cytoskeleton during the RPE degradation process is relatively sparse.…”
Section: 0 Phagocytosis In the Retinal Pigment Epithelial Cellsmentioning
confidence: 99%
“…The most widely understood mechanism is the disruption of crystallin solubility and/or stability directly by mutations/modifications or indirectly by changes in cellular homeostasis. It is worth noting that mutations in some of the crystallin genes have been associated with non-cataract abnormities such as neurodegenerative diseases, cardiomyopathy, tumorigenesis and retinal and vascular disorders [23][24][25][26]. Similar to proteins involved in neurodegenerative diseases, crystallins can also form amyloidlike fibrils under certain solution conditions [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, crystallin location and function in the retina and RPE have been described [Sakaguchi et al, 2003;Organisciak et al, 2011;Zigler et al, 2011;Sreekumar et al, 2010;Gangalum et al, 2011]. A-and B-crystallin are located in the ganglion cell layer and photoreceptor layer, whereas -crystallin is detected in all nuclear layers of the retina [Xi et al, 2003].…”
Section: Amdmentioning
confidence: 99%